Formação continuada de professoras da educação básica: produção discursiva na pesquisa acadêmica (1997-2018) - Pedro, Fabiane Bitello (Universidade do Vale do Rio dos Sinos, 2020)
This dissertation analyses the discourses that anchor the academic production on the continuing education of Brazilian female teachers of basic education and in what ways these discourses constitute what is understood as teaching between the years 1997 to 2018. The research is based on the fields of teaching studies, teacher training studies and the post-structuralist perspective. Documentary research is used as a methodological procedure to examine empirical material, consisting of six academic papers (five dissertations and one article linked to a PPG research). To analyse the complex web of discourses, present in the empirical material, three analytical categories were organised: I – continuing education in the context of the market, which is anchored in the legal aspects that regulate and sometimes bureaucratise Brazilian education, especially the very context of continuous professional development, bringing out, among other senses, the training articulated to entrepreneurship of the self; II - in a context of ad aeternum continuing education, it is possible to show that less than 40% of Brazilian female teachers, according to INEP data for the year 2017, had access to some type of continuing education, which further underscores the idea that they should act on themselves and take individual responsibility for their own training process; III - as a last category, the authorship and the (re)creation of continuing formation enables us to identify and analyse other ways in which female teachers relate to the formative spaces to which they have access and how the ethos of formation is constituted in this journey.
Keywords: Formação; Formação continuada; Docência; Educação básica; Discurso; Training; Continuing education; Teaching; Basic education; Discourse; ACCNPQ::Ciências Humanas::Educação